Ethical Aspects of Music Teaching - Čuš, Tjaša (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter addresses key ethical challenges in music education, including respecting copyright, preventing cultural appropriation, ensuring transparent and fair assessment, and promoting ethical behavior among students. Teachers must recognize the importance of copyright, as violations harm creators' rights and the use of music without proper permissions is prohibited, except in limited circumstances. Cultural appropriation, which can trivialize cultural expressions, requires a sensitive and informed approach. Teachers should understand the cultural context of musical works, involve local cultural representatives, and encourage critical reflection among students, enabling them to distinguish between cultural exchange and appropriation. Transparency and fairness in assessment foster trust and motivation in students, while ethical education promotes the development of empathy, moral awareness, and critical thinking. By guiding students ethically, teachers contribute to their understanding of cultural values and help shape conscious, respectful individuals.